Distingsi dan Diaspora Tasawuf Abû al-Ḥasan al-Shâdhilî - Saifulah, Saifulah (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2014)
This article discusses Shâdhilîyah, one of the most recognized sufi orders, which possesses quite distinct aspects in the conception of its mystical teachings. This sufi order was founded by Abû al-H}asan al-Shâdhilî, a sufi who has moderate and open view of the worldly life. Al-Shâdhilî explained about how a sufi should behave towards and deal with worldly matters. Although al-Shâdhilî asserted that a person who practice tasawwuf should not pay more adoration on the worldly matters (hubb al-dunyâ), the person does not have to abhor and leave such lively aspects as wealth and position behind. The most important thing to a sufi, according to al-Shadhili, is how he obeys the requirements of shar? by avoiding away from immoral deeds and at the same time recognizing God in his heart (ma?rifat Allâh). Al-Shâdhilî initiated tasawuf ?amalî which is affiliated to the Ahl al-Sunnah wa al-Jamâ?ah school, an Islamic mystical thought that adheres to the principles of sharî?ah based on the foundation of al-Qur?ân dan H}adîth. The concept of al-Shâdhilî?s tasawuf has been subsequently revealed into the great sufi order spectrum, namely al-Shâdhilîyah, where during its historical development this sufi order has led to the emergence of many branches with different names. Keywords: Shâdhilîyah, open view, hubb al-dunyâ, ma?rifat Allâh.